The Repurchase Intention Development: the Case of Birds Nest Market Consumers in China - Rahman, Nik Khadijah Nik Abdul; Zandi, GholamReza; Yuan, Liang (International Journal of Engineering and Technology, 2018)
This research proposed a model for understanding the factors influencing customer repurchase intention in Chinese birdâ€™s nest market, addressed the issue related to customer repurchase intention and customer loyalty. Total 120 people chosen for data collection and probability sampling technique applied for data collection. For the sample of this research, this research study focus on Chinese consumers who originally come from China mainland. Â The questionnaire firstly was developed in English, and then translated into a Chinese version in order to target the Chinese consumers. Data analysis performed on SPSS and results are in support of all the critical factors such as customer satisfaction, switching barrier and advertisement that has positive influence on the customer repurchase intention. The proposed model confirmed the relationship between all dimensions such as customer satisfaction, customer trust, switching barriers, advertisement, and repurchase intention. From a theoretical perspective, findings suggest that the customer satisfaction and trust can be represented as post-consumption beliefs and the switching barriers and advertisement is applicable for studying post purchase phenomena, such as repurchase intention and loyalty.